Analisis dan Perancangan Sistem Informasi Point Of Sales Berbasis CRM - Muhammad Ardiansyah (Universitas Internasional Batam, 2019)
In the era of globalization, which is now increasingly rapid, making customers in a company smarter and more and more demanding. With the existence of technology also makes companies easily interact with customers. The company must have good service and relationships with its customers in order to always meet the needs of its customers. So from that make an information system that can help companies in this study is a minimarket as a businessman to be able to maintain relationships with customers. With this system, later it will be able to attract new customers to interact and transactions in minimarkets and existing customers will become more loyal in conducting transactions at minimarkets. This information system will use system creation methods, namely the waterfall method, which is part of the SDLC (System Development Life Cycle) which can help system developers make it easier to analyze and design systems. The application used for this information system is Microsoft Visual Studio 2010 and uses the VB.NET language as a front end and Microsoft SQL Server 2008 Express R2 as a database or data storage system and uses Enterprise Architect to describe the UML (Unified Modeling Language) diagram. This information system provides several solutions to problems faced by minimarkets such as transaction recording, tidier customer data management. Conclusions obtained by the existence of a customer relationship management system integrated with point of sales, minimarkets can improve service to customers by providing the information needed quickly and precisely.